Event Concept Planning Based on Marine Tourism in Mallasoro Village, Jeneponto Regency - Hamzah, Amiruddin; Muchlis, Nur Farah Fajriaty; Rohma, Irva Yulia (Media Wisata, 2024)
This study aims to identify the potential of marine tourism and design an event concept that can enhance the welfare of the local community in Mallasoro Village, Jeneponto Regency, South Sulawesi. Using a qualitative approach with descriptive methods, data was collected through in-depth interviews, observations, and documentation. SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) assessed the strengths, weaknesses, opportunities, and threats involved in developing the event concept. The analysis reveals that Mallasoro Village has significant strengths, including natural beauty, a strong local culture, and community support. However, challenges were identified, such as inadequate infrastructure and limited tourism promotion. Opportunities include the growing interest in marine tourism and regional government support through policies and capacity-building programs. Threats, such as climate change affecting beach and ocean conditions and competition with other destinations in South Sulawesi, must be anticipated. With proper planning, Mallasoro Village has the potential to become a leading marine tourism destination by developing Leisure Events and Cultural Events that incorporate diverse attractions and innovative programs, including sports, tours, education, workshops, exhibitions, culinary festivals, and sustainable marine conservation activities. These efforts can increase tourist visits while strengthening environmental awareness.